JERUSALEM AS A PLACE OF EXILE DURING THE MAMLUK ERA - Abu-Munshar, Maher Y. (Journal of Al-Tamaddun, 2019)
Jerusalem fell to the Mamluks in the year ce 1260. Up until then the Ayyubids had been ruling the holy city ever since Salah al-Din had liberated it from the Crusaders in ce 1187. Under Mamluk rule, which lasted for nearly 250 years, Jerusalem’s centrality and importance were restored, though they had greatly diminished under some Ayyubid rulers. While the Mamluks made substantial contributions to Jerusalem by building and maintaining mosques (masajid), convents (zawaya), Sufi centres (khawaniq), schools (madaris), hospitals and hospices, under their jurisdiction Jerusalem also became a place of temporary or permanent exile for out-of-work dignitaries and retired princes, army commanders and others who had lost favour with the sultans. In this article I present a critical analysis of their reasons for choosing Jerusalem as a place of exile and focus on the following questions. When and why did the Mamluks designate the city as a place of exile? Who was exiled, when, and why? How dangerous were the exiles? And what, if any, contribution did they make to Jerusalem’s development at that time?